Current understanding of the factors influencing the functional independence of people with cerebral palsy: a review of the literature. (3rd April 2017) - Posłuszny, Adam; Myśliwiec, Andrzej; Saulicz, Edward; Doroniewicz, Iwona; Linek, Paweł; Wolny, Tomasz
Abstract : Background: The variation in functional independence of people with cerebral palsy (CP) allows us to state that there are various factors influencing the development of this independence. Objective: The purpose of this study was to analyze scientific articles focused on the search for factors influencing the functional independence of people with CP in the context of planning the rehabilitation procedures. Methods: The Medline, PubMed, EBSCO, and ScienceDirect electronic databases were searched for articles on factors influencing the functional independence of people with CP. Inclusion criteria used in searching were: articles in English and articles on people with CP. Exclusion criteria were: no access to full, free version of the article and articles published before 1990. Results: Three groups of factors influence the development of functional independence: internal, external, and task-based factors. External and task-based factors will be of greatest interest to specialists dealing with the rehabilitation of people with CP, as these are the factors which can most readily be changed, and thus offer the best opportunity to increase the independence of people with CP. Conclusions: Factors, which affect the functional independence of people with CP, are important in planning rehabilitation since they enable professionals in motor rehabilitation to be focused on factors that are amenable to change. Those factors allow professionals in the field of physical rehabilitation to be driven by goals, which are directly related to improving the functional independence of people with CP.